Implementation of Tahfidz-Based Islamic Boarding School - Nuryahman, M.; Supriyoko, Supriyoko; Mulyo, Mufrod Teguh (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2022)
This study aims to determine the development of boarding school management and its implications as an effort to improve the quality of Islamic school and their relevance to Islamic education goals. The research method used is field research with qualitative research. Data collection technique use observation, documentation and in-depth interviews while testing the validity of the data uses source triangulation techniques. The results of this study indicate that the implementation of the Islamic boarding school model with the addition of a special program in the form of tahfidzul Qur'an and its implication is a real effort by schools in improving Islamic schools. It has significant relevance to the goals of Islamic education conceptually and the values ​​of Islamic education in Islamic school in fulfilling aspects of student management developed from the goals of national education.